The case for measuring antibodies to specific citrullinated antigens. - Montgomery, AB; Venables, P; Fisher, B (2013)
Anti-citrullinated protein/peptide antibodies (ACPA) are the principal autoantibody system associated with rheumatoid arthritis (RA), with diagnostic sensitivity of 70% and specificity of 95%. Current testing for ACPA uses the anti-cyclic citrullinated peptide assay (anti-CCP) which measures a generalized reactivity with citrulline-containing peptides, thus giving no insight into reactivity to specific RA antigens. Of these, the best characterized are, α-enolase, fibrinogen/fibrin, vimentin, Type 2 collagen and filaggrin, antibodies to each of which are found in approximately 30-60% of RA cases. Given reports of cross-reactivity between citrullinated antigens, we discuss whether or not measuring these specific antibodies could aid: clinical diagnosis, identification of clinical subsets and drug responses, or provide insight into pathogenic mechanisms or etiology of RA.